Martin Paul EVE, Close Reading with Computers. Textual Scholarship, Computational Formalism and David Mitchell’s Cloud Atlas, Stanford University Press, 2019 - Al Refaei, Salma (Metacritic Journal for Comparative Studies and Theory, 2020)
The term “distant reading” is an approach to literary studies that applies reductive and labor-saving computational methods to literary data. It uses the tireless repeatability of computational tasks in order to amass “statistically informed deductions about novels or other works that one has not read” (3). Given the fact that nowadays more books are being published than one has the physical capacity to read in a lifetime, distant reading comes as a tool to help us cope with the amount of published work; in this sense it is an “antinecrotic practice” (3) as it staves off the limiting effects of death. However, it can also be interpreted as an “antireading practice” (4) because it substitutes the direct, human engagement with literature.